A JOURNEY OF FINDING EXISTENCE IN RELATION TO LOVE LIFE AS PORTRAYED IN MURAKAMI’S SPUTNIK SWEETHEART - Benedicta Stella Fortunae; Susanne A.H. Sitohang (Prodi Sastra Inggris UKI, 2019)
The existence of one person is an absolute aspect for human beings to acknowledge. It is a portrayal of one's life purpose. Self-existence is not easily obtained, and it requires a long process of self-discovery. One of the ways to find one's identity could be perceived by the journey of love, as experienced by the main character in Sputnik Sweetheart, namely K. Love has an important aspect in determining one's life. The Author, Haruki Murakami, became popular after writing many topics about the search for identity with the touch of Surrealism and Nihilism in his works. This research examines the search for self-existence from the narrator's love experiences, K. It also aims to explain types of love according to Ancient Greece, how Eros collides with Platonic love through the lens of the main character, and the types of love aforementioned connected with the journey of self-discovery. By reading this research, the readers will have comprehensive knowledge about understanding self-discovery through love. The journey of love in one's life could be the purpose of life because love colors life, and it is the principle of self-discovery.